Luteolin improves the systolic and diastolic functions of the thoracic aortic vessels in type 2 diabetic rats through the Kv7.1 channel - Li, Weiping; Yang, Zerong; Wang, Xingru; Guo, Pengmei; Wu, Li; Wang, Yanru; Lyu, Yue; Xu, Xiaojia; Ji, Haijie (Frontiers in Pharmacology, 2025)
ObjectivesThis study aimed to evaluate the therapeutic effects of luteolin (Lut) on vascular dysfunction in type 2 diabetic rats and explore its underlying mechanisms, particularly its regulation of the myogenic response in thoracic aortic vessels via the Kv7.1 (KCNQ1) channel.MethodsType 2 diabetes mellitus (T2DM) was induced in rats via high-fat/high-glucose diet combined with intraperitoneal streptozotocin (30 mg/kg). Animals were assigned to four groups: normal control (NC), NC + Lut (80 mg/kg), diabetic (DM), and DM + Lut. Fasting blood glucose, body weight, lipid profile, and blood pressure were monitored. Myogenic response of the thoracic aorta was assessed using vascular ring tension assays. Expression of KCNQ1 was evaluated via qRT-PCR. In vitro, A7r5 cells were cultured under normal (5.5 mM) or high glucose (30 mM) conditions, with or without the addition of chromanol 293B (Kv7.1 inhibitor) or PDBu (PKC agonist), the effects of Lut on the expression of KCNQ1 and Kv7.1 were observed by qRT-PCR and cellular immunofluorescence assay.ResultsLuteolin significantly reduced fasting blood glucose, lowered blood pressure, and improved lipid parameters in diabetic rats. It attenuated the enhanced vasoconstriction and impaired vasodilation observed in DM rats. KCNQ1 expression was downregulated in DM rats but restored by Lut treatment. In A7r5 cells, Lut increased KCNQ1 and Kv7.1 expression, which was inhibited by high glucose or PKC activation.ConclusionLuteolin improves vascular tone and function in diabetic rats by restoring Kv7.1/KCNQ1 expression, possibly through inhibition of PKC signaling. These findings highlight Kv7.1 as a potential therapeutic target for diabetic vascular complications.